Tata Ruang Lingkungan Kampung Batik di Jakarta sebagai Kawasan Wisata Industri Rumah Tangga - Widya Katarina; Nina Nurdiani; Yosica Mariana (Bina Nusantara University, 2014)
Research on Kampung Batik Spatial Environment in Jakarta as Household Industrial Area Tourism conducted in Kampung Batik Palbatu through descriptive approach. This study aims to identify the characteristics of the environment and the potential area of Kampung Batik in Jakarta. Data collection in the field carried out by the method of observation and the mapping of spatial design of buildings and the environtment. Data analysis was performed by descriptive analysis. The study results showed that the Kampung Batik Palbatu as batik village in Jakarta, which was conceived and developed by a community group of batik lovers, demonstrated slow development. Image or the character of the environment of the region of Kampung Palbatu as Kampung Batik is yet to be seen, since the elements of the image-forming region are not clear. The potential of the region as the region of home industry namely Kampung Batik has started there, but lacks of supports from the government, and the local community.